(NwOPROSY STRUKTURNOJ GEOLOGII (B:s (NsBORNIK STATEJ (B/s - (NrODYGIN(B, (NaLEKSANDR iWANOWI^s; (NtOMSKIJ GOS(B. (NUN(B-(NT IM(B. (Nw(B.(Nw(B. (NkUJBY[EWAs ((NtOMSK (B:s (NiZD(B-(NWO tOM(B. (NUN(B-(NTA(B,s, 1987)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NaLTAQ(B-(NsAQNSKAQ GORNAQ OBLASTXs; (NgEOLOGIQ STRUKTURNAQs